2015
DOI: 10.1007/s11999-014-3995-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional Wear and Impact-to-wear Tests of Phospholipid-polymer-grafted and Vitamin E-blended Crosslinked Polyethylene: A Pilot Study

Abstract: Background Modifying the surface and substrate of a crosslinked polyethylene (CLPE) liner may be beneficial for high wear resistance as well as high oxidative stability and excellent mechanical properties, which would be useful in contributing to the long-term performance of orthopaedic bearings. A grafted poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) layer on a vitamin E-blended crosslinked PE (HD-CLPE[VE]) surface may provide hydrophilicity and lubricity without compromising the oxidative stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In contrast, the surface roughness of the PMPC-grafted HD-CLPE(VE) sample decreased markedly (p < 0.01) to 0.71 nm. These results indicated that PMPC was successfully grafted on the HD-CLPE(VE) surface and that PMPC grafting resulted in a smoother surface [32,33].…”
Section: Resultsmentioning
confidence: 85%
“…In contrast, the surface roughness of the PMPC-grafted HD-CLPE(VE) sample decreased markedly (p < 0.01) to 0.71 nm. These results indicated that PMPC was successfully grafted on the HD-CLPE(VE) surface and that PMPC grafting resulted in a smoother surface [32,33].…”
Section: Resultsmentioning
confidence: 85%
“…No adverse effects and no revision surgery and no osteolysis were informed and observed. However, cobalt-chromium-molybdenum (Co-Cr-Mo) and cobalt-chromium (Co-Cr) alloys were used in recent studies as the head material against PMPC-grafted CLPE liner [67][68][69][70][71].…”
Section: Surface Coatingsmentioning
confidence: 99%
“…For example, a study is currently underway for the fabrication of a highly lubricious nanoscale modified surface using poly(MPC) grafting onto the surface of an antioxidative X-UHMWPE substrate involving vitamin E blending. 97,98 In 2009, Kyomoto and Ishihara discovered a special photochemical reaction with the super-engineering plastic poly(ether ether ketone) (PEEK). 99 Recently, PEEK has been the focus of major attention as new type of polymeric biomaterial, where the potential has been recognized for the substitution of metal and ceramic biomaterials.…”
Section: Future Perspectivesmentioning
confidence: 99%